Analisis kapasitas Daya Tampung Settling Pond di Pit Alfa Utara di PT. Hamparan Mulya - Ronal Berkat Tumanggor; Ferdinandus Ferdinandus (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
PT. Hamparan Mulya operates in the coal mining industry and applies an open-pit extraction system. In this mining method, managing surface water particularly rainwater is essential to ensure smooth operations. An effective drainage system is required to prevent runoff water from contaminating nearby rivers, lakes, and surrounding ecosystems. One practical approach used in mining operations is the construction of settling ponds, which function as treatment units for water collected in the sump before it is released into natural waterways. This study aims to identify the appropriate storage capacity for the settling pond and sump by analyzing rainfall data using the Log Pearson Type III method. The analysis produced a design rainfall value of 507.16 mm/day and a rainfall intensity of 56.94 mm/hour. With a catchment area of 14 km², the resulting runoff discharge reaches 30,782.16 m³/hour. Based on these parameters, the settling pond must be engineered to accommodate a total discharge of 30,782.16 m³/hour.